1976
DOI: 10.1042/bj1570781
|View full text |Cite
|
Sign up to set email alerts
|

Changes in conformation of reduced cytochrome c in neutral aqueous solution

Abstract: In neutral aqueous solution, high concentrations of alcohols perturb cytochrome c in such a way that reduction by means of ionizing radiation results in the formation of abnormal conformers of ferrocytochrome c resembling those previously seen on reduction in alkaline solution. These relax to normal ferrocytochrome c in about 0.1 s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…The data for the reduction of ferricytochrome c by dithionite is in partial agreement with the results of pulse radiolysis [5,6] where ferricytochrome c is reduced by hydrated electrons. The major difference concerns observations near neutrality where Pecht and Faraggi [S] reported slow secondary spectral changes while Land and Swallow [6] saw none.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The data for the reduction of ferricytochrome c by dithionite is in partial agreement with the results of pulse radiolysis [5,6] where ferricytochrome c is reduced by hydrated electrons. The major difference concerns observations near neutrality where Pecht and Faraggi [S] reported slow secondary spectral changes while Land and Swallow [6] saw none.…”
Section: Discussionsupporting
confidence: 79%
“…The major difference concerns observations near neutrality where Pecht and Faraggi [S] reported slow secondary spectral changes while Land and Swallow [6] saw none. Lambeth et al [3], in agreement with Land and Swallow [6], found the reduction of cytochrome c by dithionite to be biphasic only in the alkaline region, and tried to explain Pecht's data by poor control of pH in unbuffered solutions [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with several authors [5,20] we have found that the ethylene glycol and glycerol radicals do not reduce ferricytochrome c. These radicals also do not reduce metmyoglobin. After ~'-irradiation of metmyoglobin there is however a build up of a characteristic low spin spectrum.…”
Section: Irradiation In the Presence Of Ethylene Glycol And Glycerolsupporting
confidence: 81%